Advances in managing pregnancy toxaemia in sheep. Issue 2 (5th March 2021) - Crilly, JP; Phythian, Clare; Evans, Mike
Abstract : Background : Ovine pregnancy toxaemia (OPT) is a metabolic disorder of ewes in late pregnancy. Cases are typically seen in ewes carrying multiple fetuses, hence the alternative name of 'twin lamb disease'. The disease has been well known for many years. Despite this, the toll inflicted by the disease remains considerable, due both to the poor prognosis of clinically affected animals, even with appropriate treatment, and the impact of the provoking factors of under‐nutrition and concomitant disease on ewe morbidity, lamb survival and flock productivity. Cases of OPT are an indication of shortcomings in the management of late‐pregnancy ewes. Aim of the article : This article provides an update on the aetiopathogenesis, diagnosis, treatment and prevention of OPT, drawing on recently published studies.